PENGARUH BIAYA PERIKLANAN DAN PERSONAL SELLING TERHADAP PENJUALAN DEPOSITO PADA BANK MUAMALAT INDONESIA TULUNGAGUNG (An-Nisbah: Jurnal Ekonomi Syariah, 2014)
The purpose of this research is to test  infuence: (1) the expense of advertisement to improvement of deposit sale; (2) the expense of personal selling to improvement of deposit sale; (3) at the same time the expense of advertisement and the expense of personal selling to improvement of deposit sale. The research uses six sekunder data in the year 2011 up to  2013 in semester. The technique of data analysis  uses the double analysis regresi with the program SPSS 21. The fnding of the research was the expense of advertisement is not signifcant infuence to improvement of deposit sale and the expense of personal selling is signifcant infuence to improvement of deposite sale. At the same time the expense of advertisement and personal selling are signifcant infuence to improvement of deposite sale.Keywords: Expense, Advertisement, Personal Selling, Deposit